The challenge of Joseph H. Jackson: how America's most powerful Black preacher became a forgotten man - Alcántara, Jared E. (Oxford University Press, 2024)
In The Challenge of Joseph H. Jackson, Jared Alcántara offers a definitive biography of one of the most controversial, complex--and, eventually, forgotten--luminaries of the twentieth century. Alcántara chronicles Jackson's rise to power as pastor of the largest Black church in the United States, the 15,000-member Olivet Baptist in Chicago, and as the longest-tenured president of the six-million-member National Baptist Convention, at one time the nation's largest Black organization. Sociologist E. Franklin Frazier contended that holding an office like this was akin to being the president of a "nation within a nation," the president of Black America. Nicknamed the "Negro Pope" along with "Silver Tongue," Jackson was known foremost for his oratorical talents. But his significance to twentieth-century Black Christianity and U.S. history more broadly has not yet been fully understood. Alcántara here provides a compelling examination of Jackson's humble beginnings, rise to power, and gradual fall from grace. The Challenge of Joseph H. Jackson examines Jackson's political alliances, describes his controversial views on race, catalogues his global ecumenical work, explains his fallout with the family of Dr. Martin Luther King Jr., and connects his eloquence to the maintenance of power in a tradition that prizes sacred oratory. Drawing on extensive archival material from the Chicago History Museum, Alcántara deftly chronicles the life and legacy of one of the most complex figures in African American history.--Provided by publisher